Hubungan Dukungan Keluarga dengan Asupan Makanan pada Pasien Diabetes Melitus Tipe 2 di Instalasi Rawat Jalan RS Muhammadiyah Palembang - Fatima, Diva Syaidatun; Tanzila, Raden Ayu (Universitas Muhammadiyah Palembang, 2025)
Type 2 diabetes mellitus continues to be a major health problem in Indonesia. The frequency of diabetes sufferers in Indonesia is concentrated on demographic variables such as age, education level, smoking status, and body mass index (BMI). In managing type 2 DM, family support can influence daily eating patterns. Type 2 diabetes mellitus sufferers tend to pay attention to food intake and adhere to the diet if they have family support. Objective: to examine the relationship between family support and food consumption in Type 2 diabetes mellitus patients at Muhammadiyah Hospital Palembang. Method: Analytical observational research with cross sectional design. The sample was 96 people. Analysis uses an alternative chi-square test, namely Fisher's Exact. Results: The results showed that family support was the most dominant in the good category (79.2%), dietary compliance was the most dominant in the good category (72.9%), food intake was the most dominant in the good category (69.8%), and the p-value 0,000. Conclusion: there is a relationship between family support and patient food intake and there is a relationship between family support and diet compliance in Type 2 Diabetes Mellitus patients at the Muhammadiyah Hospital Palembang Outpatient Installation